Strategi Pembelajaran Berdiferensi: Akselerasi Meningkatkan Potensi Peserta Didik - Rusmala Siringoringo; Masduki Asbari; Cesilia Margaretta (Journal of Information Systems and Management (JISMA), 2023)
Abstract - The Merdeka Curriculum is synonymous with learning that supports students, as well as differentiated learning. Differentiated learning is really needed by students to carry out a learning approach that allows teachers to meet the individual needs of each student in the class. The aim of this research is to provide learning experiences that are relevant, challenging, and appropriate to the individual's level of understanding and learning style.In this study report, a qualitative descriptive method was used by listening because the data source was obtained by listening to oral narratives from the YouTube channel Young Teacher Notes entitled "Theories, Examples and Illustrations of Differentiated Learning Strategies in the Independent Curriculum". The results of this research explain that in differentiated learning students also have the freedom to increase their potential in accordance with the student's learning readiness, interests and learning profile. With Differentiated Learning, students will be able to interact with the process and results they obtain, and have good self-regulation, so that they will obtain optimal learning achievement. Teachers also demand to facilitate students according to their needs, because each student has different characteristics, so they are not given the same treatment in the learning proces Keywords: Curiculum,Freedom to learn,differentiated learning,Education.